Synthesis and Characterization of a New Mebendazole Salt: Mebendazole Hydrochloride - Brusau, Elena Virginia (2008)
Mebendazole hydrochloride [(5‐benzoyl‐1H‐benzimidazole‐2‐yl)‐carbamic acid methyl ester hydrochloride, MBZ·HCl], a new stable salt of mebendazole (MBZ), has been synthesized and characterized. It can easily be obtained from recrystallization of forms A, B, or C of MBZ in diverse solvents with the addition of hydrochloric acid solution. Crystallographic data reveals that the particular conformation adopted by the carbamic group contributes to the stability of the network. The crystal packing is stabilized by the presence of three N–H…Cl intermolecular interactions that form chains along the b axis. The XRD analyses of the three crystalline habits found in the crystallization process (square‐based pyramids, pseudohexagonal plates, and prismatic) show equivalent diffraction patterns. The vibrational behavior is consistent with crystal structure. The most important functional groups show shifts to lower or higher frequencies in relation to the MBZ polymorphs. The thermal study on MBZ·HCl indicates that the compound is stable up to 160°C approximately. Decomposition occurs in four steps. In the first step the HCl group is eliminated, and after that the remaining MBZ polymorph A decomposes in three steps, as happens with polymorphs B and C.